2016
DOI: 10.1016/j.tjog.2015.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Are congenital malformations more frequent in fetuses with intrahepatic persistent right umbilical vein? A comparative study

Abstract: Our rate of malformations associated with I-PRUV (17.9%) is similar to previously published rates. I-PRUV has shown a significant increase in the rate of associated malformations, although this association has only been found to be statistically significant in the genitourinary system. Noteworthy is the fact that this comparative study has not pointed to a significant increase in the congenital heart malformation rate. Diagnosis of isolated I-PRUV does not carry a worse prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 14 publications
8
13
0
Order By: Relevance
“…The most common anomalies in PRUV fetuses were cardiovascular system anomalies, followed by nervous system, urinary system, skeletal, and other anomalies. Similar to our study, Adiego-Calvo et al 6 found a statistically signi cant association between isolated PRUV and the presence of congenital malformations, but in their series, only malformations of the genitourinary system showed this positive association. The difference in sample size may be the main reason for the different results.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The most common anomalies in PRUV fetuses were cardiovascular system anomalies, followed by nervous system, urinary system, skeletal, and other anomalies. Similar to our study, Adiego-Calvo et al 6 found a statistically signi cant association between isolated PRUV and the presence of congenital malformations, but in their series, only malformations of the genitourinary system showed this positive association. The difference in sample size may be the main reason for the different results.…”
Section: Discussionsupporting
confidence: 91%
“…PRUV can appear in isolation or concomitantly with anomalies in other systems. Our study shows that approximately 13.5% of PRUV fetuses have anomalies in other systems, similar to the concomitant malformation rate of 13% reported by Blazer et al 12 or 17.9% reported by Adiego-Calvo et al 6 , and was lower than the rate of 23.5-40.9% reported by other researchers. 1,2,9,10 The lower proportion of PRUV fetuses with concomitant anomalies observed in our study may be due to the following: rst, our study included cases at late gestation, while some fetuses with PRUV and concomitant serious anomalies might have been aborted during early or mid-gestation or had stopped growing in utero.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations